Efeitos de condições de monitoramento de mães sobre desempenho em supervisão de estudos - Christovam, Ana Carolina Camargo (2011)
Studies on school problems and school failure suggest that some of these problems are result of ineffective interactions between student, family and school. This is a serious concern for the educational practices, as parental involvement is also indicated as desirable behavior of parents and that has important impacts for the children's school performance. In this way, the Homework has been the subject of several studies since that role both in academic performance, and as a communication tool between school and families, and as a strategy for promoting parental involvement. Thus, to effect an action that helps the practice of parents in the education of the child, especially in the habits of study, was proposed in this study to evaluate the contingencies arranged by parents in the installation and maintenance of home study behaviors, to interfere with these contingencies from a set of interventions and assess the differential impact of these interventions for the performance of parents also tried to verify possible changes in the child's behavior due to the change in the behavior of mothers. Study participants were the teacher, three students in the first year of elementary school at a municipal school in a town in the state that had begun a project in Homework and their mothers. To perform the study, it were used a multiple-baseline design, with gradual introduction of three different experimental conditions (preparation methods for parents to deal with behaviors of study), and held subsequent sessions of the introduction of observation conditions. For data analysis, the behaviors of interest were selected according to the literature and organized in order to organize the data into five categories: behaviors related to place of study, behaviors related to study material, behaviors related to execution of task, behaviors in need of help, and behaviors related to mother-child relationship during the task. Data were analyzed for each Dyad, comparing the data obtained at different stages, and by comparing the impacts possibly generated by each of the stages in the mother's behavior to monitor for their children. It was also found possible changes in the performance of participating students from the change in behavior of mothers as educators. The results indicate the relevance of the procedure tested for promoting appropriate behavior study and was effective in modifying some aspects of the behavior of all Dyads: To observe the completion of the task, the child's manifestation of humor, Moment of providing materials, subject responsible for providing materials and subject responsible for organizing materials. Behavioral changes occurred in at least two of Dyads in relation to: quality of help offered by the mother in carrying out the task, quality of help offered in the correction of the task and the adequacy and quality of the child. It may also receive help in accomplishing the task. These results show the importance of all the conditions for the training of parents as educational agents, showing better results than the conditions seen isolated.